QUALITY WORK OF LIFE DALAM MENINGKATKAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR, DAN KINERJA KARYAWAN - Ryan Pahlawan (Jurnal Ilmiah Ekonomi Dan Bisnis, 2023)
This study aims to analyze the effect of quality work on organizational citizenship behavior and employee performance. The sample for this research is government-owned credit insurance employees in Riau Province, totaling 324 people. The technique used is the census method. The data analysis technique used is SEM-PLS. The results of this study indicate that a) quality of work life has a positive and significant influence on organizational citizenship behavior; b) quality of work life has a positive and significant influence on employee performance; c) organizational citizenship behavior has a positive and significant influence on employee performance; and d) quality of work life has a positive and significant influence on employee performance through organizational citizenship behavior. Based on the results of this study, companies must pay extra attention to employees, especially in a comfortable work environment, in order to create an increase in organizational citizenship behavior and employee performance